Grip strength: are dinamometers equivalent? JAMAR vs E-Link - Tomás, Maria Teresa (2013)
Levels of risk for future disability can be assessed with grip strength. This assessment is of fundamental importance for establishing prevention strategies. It also allows verifying relationships with functional capacity of individuals. Most studies on grip strength use the JAMAR Hydraulic dynamometer that provides the value of isometric force obtained during the performance of grip movement and is considered the “gold standard” for measurement of grip strength. However, there are different dynamometers available commercially, such as portable computerized dynamometer E-Link (Biometrics), which provides the value of maximum force (peak force) in addition to other variables as the rate of fatigue for hand strength, among others. Of our knowledge, there are no studies that allow us to accept or not and compare values obtained with both devices and perhaps use them interchangeably. The aim of this study was to evaluate the absolute agreement between the measurements of grip strength (peak force or maximum force in kg) obtained from two different devices (portable dynamometers): a computerized (E-Link, Biometrics) and one hydraulic (JAMAR).